Fibroblast growth factor-21: Preserving cell viability in diabetic neuropathy through the AKT/PI3K cellular pathway (Annals of Medical Research, 2024)
Aim: This study aims to investigate the potential neuroprotective effects of fibroblast growth factor-21 (FGF21) on dorsal root ganglion (DRG) neurons under high glucose (HG) conditions, mimicking diabetic neuropathy. Specifically, we hypothesize that FGF21 enhances cell viability and reduces glucose-induced neuronal death via the activation of the phosphatidyl-inositol-3-kinase (PI3K)/AKT signaling pathway.Materials and Methods: Primary DRG neurons were cultured from laboratory models and exposed to HG concentrations to simulate diabetic conditions. Various concentrations of FGF21 were administered to the DRG neurons. Cell viability was assessed using the MTT assay (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide), a widely used enzymatic method for determining cellular metabolic activity. The involvement of the PI3K/AKT signaling pathway in mediating the effects of FGF21 was also examined through biochemical assays and pathway inhibitors.Results: Administration of FGF21 to DRG neurons exposed to HG conditions significantly protected cell viability and reduced glucose-induced neuronal death (p